Synthesis and electrochemical studies of NaCoPO4 as an efficient cathode material using natural deep eutectic solvents for aqueous rechargeable sodium-ion batteries - Eswara Rao, C. V. V.; Janardan, Sannapaneni; Manjunatha, H.; Venkata Ratnam, K.; Kumar, Sandeesh; Chandrababu Naidu, K.; Ranjan, Shivendu (Frontiers in Chemistry, 2024)
In this work, sodium cobalt phosphate (NaCoPO4) is successfully prepared by a costeffective ionothermal method using deep eutectic solvent (DES) for the first time. The synthesized NaCoPO4 is used to fabricate a cathode material for aqueous rechargeable sodium-ion batteries.The surface morphology of the prepared materials and its compositional analysis are done by using FESEM and EDX analysis respectively. The XRD, SEM and EDX studies reveal that the material has orthorhombic-shaped particle morphology with uniform distribution and is in nanoscale (approximately 50nm). The nature of the cation inserted (Na + Ion insertion) was confirmed by recording CV profiles at different concentrations of Na2SO4 electrolyte. The reversibility of the electrode redox reaction was studied by varying the scan rate in CV studies and found that the electrode exhibits a reversible behavior with a resistive behavior. In GCPL studies, the cell TiO2/2MNa2SO4/NaCoPO4 shows a significant reversibility with a prominent discharge capacity of 85 mAh g -1 at 0.1C and 88% of capacity retention after 100 cycles. Thus, the prepared materials could be behaved as an effective futuristic alternative battery material for rechargeable batteries.